Filozoficzna refleksja nad istotą informatyki - Stacewicz, Paweł (Człowiek i Społeczeństwo, 2025)
The paper is a review of Izabela Bondecka-Krzykowska’s book entitled „O przedmiocie badań informatycznych. Studium filozoficzne” (eng. “On the subject of computer science research. A philosophical study”). It discusses the main theses of the book, the composition of the content in individual chapters and suggestions for topics that could be taken up in subsequent editions of the monograph. A number of polemical remarks were also formulated.